2012
DOI: 10.2478/v10304-012-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

The knit on demand supply chain

Abstract: The knit on demand supply chain As customers’ tastes become more differentiated, so must companies’ offerings evolve. The demand for variety may soon become unmanageable, and several companies are addressing this trend by adopting a system of mass customization. One project, Knit on Demand, has been conducted by the Swedish School of Textiles in close collaboration with a knitting company and a retailer of tailored fashion in Stockholm. Production and sales of customized products pose logistical chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The data was collected by interviews and analysed by the data triangulation method and it proved to be consistent with previous studies in the area by Peterson, Mattila [19] and Larsson et al [20]. The data presented in Table 2 shows that the sell-through factor is almost 90-100%, compared to the average of 65-70% in ordinary fashion retailing [9].…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The data was collected by interviews and analysed by the data triangulation method and it proved to be consistent with previous studies in the area by Peterson, Mattila [19] and Larsson et al [20]. The data presented in Table 2 shows that the sell-through factor is almost 90-100%, compared to the average of 65-70% in ordinary fashion retailing [9].…”
Section: Resultssupporting
confidence: 59%
“…The data were triangulated with the results from two other studies on mass customisation of knitted products [19,20].…”
Section: Methodsmentioning
confidence: 99%
“…Such an expense may be too much for a small company, as we found in the Knit-on-Demand project (Article 4). Larsson [26] concluded that most customers were not concerned about lead-times or price. On the other hand, offering to deliver a customised garment in 3 to 5 hours (see Article 1) might it be a considerable advantage for a retailer.…”
Section: Resultsmentioning
confidence: 99%
“…Article 4 [26], describes Knit-on-Demand case study from a supply chain perspective and considers design, technology, logistics, and performance and was published in Autex Research Journal in 2012.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Lean Six Sigma is a combination of two powerful continuous improvement methodologies: Lean Management and Six Sigma. Lean philosophy focuses on reducing wastes and lead time through the operational process [1], while Six Sigma removes defects and increases quality. Each of these methodologies has become popularized individually by its successful implementation at pioneer companies such as TOYOTA and General Electric [2].…”
Section: Introductionmentioning
confidence: 99%